2019
DOI: 10.14474/ptrs.2019.8.4.187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual reality combined with balance training on upper limb function, balance, and activities of daily living in persons with acute stroke: a preliminary study

Abstract: The aim of this preliminary study was to investigate the effects of virtual reality combined with balance training on upper limb function, balance, and activities of daily living (ADL) in persons with acute stroke. Design: Randomized controlled trial. Methods: Fourteen acute stroke survivors were recruited and randomly assigned into two groups: the experimental group (n=7) and the control group (n=7). Both groups performed the conventional rehabilitation therapy for 30 minutes a day, 5 times a week, for 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Posttreatment balance in the VR group had a mean value of 36.62 (SD 7.76), as compared to the routine physical therapy group (mean 26.94, SD 6.46). Similar results were seen in a study conducted by Jeon et al [ 23 ] that suggested that VR in combination with balance training had significant improvement in patients with stroke as compared to the VR alone. Another study conducted by Aramaki et al [ 24 ] showed that VR training improved balance and upper limb function, and improved the quality of life in patients with stroke, who also reported that VR is more effective in improving dynamic balance as compared to conventional treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Posttreatment balance in the VR group had a mean value of 36.62 (SD 7.76), as compared to the routine physical therapy group (mean 26.94, SD 6.46). Similar results were seen in a study conducted by Jeon et al [ 23 ] that suggested that VR in combination with balance training had significant improvement in patients with stroke as compared to the VR alone. Another study conducted by Aramaki et al [ 24 ] showed that VR training improved balance and upper limb function, and improved the quality of life in patients with stroke, who also reported that VR is more effective in improving dynamic balance as compared to conventional treatment.…”
Section: Discussionsupporting
confidence: 89%
“…The mean age of the participants ranged from 45.91 to 65.26 yrs in the VR-based exercise group 19,20 and 49.16 to 63.50 yrs in the control group. 19,21 Three studies included patients with acute/subacute stroke (<3 mos) [22][23][24] and 11 targeted patients with chronic stroke (≥6 mos). [19][20][21][25][26][27][28][29][30][31][32] Comparison were made before and after interventions in 11 studies, and comparisons were conducted before, after interventions, and at follow-up of patients by Morone et al, 23 de Rooij et al, 24 and Yatar and Yildirim.…”
Section: Resultsmentioning
confidence: 99%
“…The score ranged from 0 to 100. A high score indicated high ADL ability [ 18 ]. The intertester and intratester reliabilities of this index were in the ranges of 0.93–0.98 and 0.87–1.00, respectively [ 18 ].…”
Section: Methodsmentioning
confidence: 99%